Propofol disrupts cell carcinogenesis and aerobic glycolysis by regulating circTADA2A/miR-455-3p/FOXM1 axis in lung cancer - Zhao, Huaping (Cell Cycle, 2020)
The involvement of propofol and circular RNAs (circRNAs) in lung cancer progression has been identified. However, the relationship between propofol and circRNAs as well as the underlying molecular mechanisms on lung cancer development remain unclear. Cell viability, migration and invasion were measured by cell counting kit-8 assay, 5-bromo-2-deoxyuridine (BrdU) and transwell assay. Glycolytic metabolism was calculated by measuring the glucose consumption, lactate production and extracellular acidification. Western blot was used to detect the protein of glucose transporter 1 (GLUT1), glycolysis enzymes, and forkhead box M1 (FOXM1). The expression of circRNA transcriptional adaptor 2A (circTADA2A), microRNA (miR)-455-3p and FOXM1 mRNA was detected by quantitative real-time polymerase chain reaction. The interaction between miR-455-3p and circTADA2A or FOXM1 was analyzed using the dual-luciferase reporter assay. Murine xenograft model was established to perform in vivo experiments. We found propofol treatment alleviated lung cancer cell proliferation, migration, invasion and aerobic glycolysis in vitro as well as inhibited tumor growth in vivo. Propofol decreased the level of circTADA2A and exerted anti-tumor effects by regulating circTADA2A. MiR-455-3p directly interacted with circTADA2A and FOXM1 in lung cancer cells, and circTADA2A could regulate FOXM1 expression by binding to miR-455-3p. Subsequently, rescue assay showed that propofol inhibited cell proliferation, migration, invasion and aerobic glycolysis by regulating circTADA2A/miR-455-3p/FOXM1 axis in lung cancer. Collectively, propofol suppressed cell carcinogenesis and aerobic glycolysis by regulating circTADA2A/miR-455-3p/FOXM1 axis in lung cancer, providing an effective clinical implication for propofol to prevent the development of lung cancer.